Proteomic Analysis and Virulence Assessment of Granulicatella adiacens Secretome - Karched, Maribasappa; Bhardwaj, Radhika G.; Tiss, Ali; Asikainen, Sirkka (Frontiers in Cellular and Infection Microbiology, 2019)
Despite reports on the occurrence of Granulicatella adiacens in infective endocarditis, few mechanistic studies on its virulence characteristics or pathogenicity are available. Proteins secreted by this species may act as determinants of host-microbe interaction and play a role in virulence. Our aim in this study was to investigate and functionally characterize the secretome of G. adiacens. Proteins in the secretome preparation were digested by trypsin and applied to nanoLC-ESI-MS/MS. By using a combined mass spectrometry and bioinformatics approach, we identified 101 proteins. Bioinformatics tools predicting subcellular localization revealed that 18 of the secreted proteins possessed signal sequence. More than 20% of the secretome proteins were putative virulence proteins including serine protease, superoxide dismutase, aminopeptidase, molecular chaperone DnaK, and thioredoxin. Ribosomal proteins, molecular chaperones, and glycolytic enzymes, together known as “moonlighting proteins,” comprised fifth of the secretome proteins. By Gene Ontology analysis, more than 60 proteins of the secretome were grouped in biological processes or molecular functions. KEGG pathway analysis disclosed that the secretome consisted of enzymes involved in biosynthesis of antibiotics. Cytokine profiling revealed that secreted proteins stimulated key cytokines, such as IL-1β, MCP-1, TNF-α, and RANTES from human PBMCs. In summary, the results from the current investigation of the G. adiacens secretome provide a basis for understanding possible pathogenic mechanisms of G. adiacens.